Characteristics and mechanisms of summer subsurface marine heatwaves in the East/Japan Sea - Li, Zhiyuan; Cui, Yan; Wu, Gangfeng; Liu, Dakang; Ren, Gang; Xu, Chang; Long, Yu; Zhu, Xiao-Hua (Frontiers in Marine Science, 2025)
This study investigated the summer subsurface marine heatwaves (SSMHWs) in the East/Japan Sea (EJS) using the Japan Coastal Ocean Predictability Experiment 2 ocean reanalysis datasets during 1993–2023. Climatologically, the cumulative (maximum) intensity area-averaged over the EJS ranges from 20°C days (2.5°C) at surface to its maximum of 36°C days (4°C) at approximately 70 m, confirming significant subsurface intensification of summer MHWs. Compared with the almost uniform spatial patterns at surface, the intensities of MHWs at subsurface layers show substantial spatial variations. The SSMHWs in the EJS are caused not by surface atmospheric forcings, but primarily by internal oceanic processes. During summer, the strong stratification in the EJS inhibits the vertical mixing and traps more heat fluxes at surface. As the main heat sources of the upper ocean, the Tsushima Warm Current (TWC) plays a crucial role in triggering SSMHWs in the EJS. Anomalous increased volume transport of TWC carries more warm water into the EJS, favoring the basin-scale intense SSMHWs. This warm water is redistributed by the East Korean Warm Current and mesoscale eddies, leading to regional features of SSMHWs in the EJS. Our results highlighted the roles of oceanic circulation in forming intense SSMHWs in the EJS.